Hubungan Digital Jealousy dengan Relationship Anxiety pada Emerging Adults Pengguna Media Sosial - Evania Eklesia Senduk; Vania Ardelia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The rapid growth of social media has transformed the dynamics of romantic relationships, particularly among individuals in emerging adulthood. Digital interactions allow partners to monitor, compare, and interpret each other’s online activities, which may trigger new forms of jealousy known as digital jealousy. This phenomenon is closely associated with relationship insecurity, especially among individuals who are prone to anxious attachment and excessive concern about their romantic relationships. This study aimed to examine the relationship between digital jealousy and relationship anxiety among social media-active emerging adults. A quantitative correlational design was employed involving 240 participants aged 18–29 years who were currently or had previously been involved in a romantic relationship and actively used social media. Participants were selected using purposive sampling, and data were collected through an online questionnaire accompanied by informed consent. Digital jealousy was measured using the Digital Jealousy Scale (DJS), while relationship anxiety was assessed using the Experiences in Close Relationships-Revised (ECR-R). Data were analyzed using Pearson correlation after the normality assumption was fulfilled. The results revealed a significant positive relationship between digital jealousy and relationship anxiety. These findings indicate that emerging adults who experience higher levels of jealousy triggered by partners’ digital activities tend to report higher levels of anxiety in romantic relationships. This study highlights the importance of understanding digital jealousy as a psychological factor that may affect emotional security in romantic relationships. The findings provide practical implications for relationship counseling, digital literacy, and psychoeducation programs aimed at helping emerging adults develop healthier patterns of social media use and more adaptive emotional regulation in romantic relationships.